Telomere dynamics in adult hematological malignancies - Olbertova, Helena; Plevova, Karla; Stranska, Kamila; Pospisilova, Sarka (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2019)
Telomeres are repetitive DNA sequences protecting physical ends of linear chromosomes against degradation and end-to-end chromosomal fusion. Telomeres shorten with each cell division, which regulates the cellular lifespan in somatic cells and limits their renewal capacity. Cancer cells are often able to overcome this physiological barrier and become immortal with unlimited replicative capacity. In this review, we present current knowledge on the role of telomeres in human aging with a focus on their behavior in hematological malignancies of adults. Associations of telomere length to age-related diseases and to the prevention of telomere shortening are also discussed.
Keywords: Cell Division; chromozomální nestabilita; Humans; telomerasa; Hematologic Neoplasms; telomere; telomery; stárnutí buněk; Biomarkers, Tumor; lymphoma; Telomerase; dospělí; stárnutí; Chromosomal Instability; lidé; Aging; telomerase; hematologické nádory; leukemia; nádorové biomarkery; Adult; Telomere; hematooncology; Cellular Senescence; aging; buněčné dělení